Meta-analysis of Project Based Learning Models on 21st-Century Student Skills - Nurazizah, Rizkiana; Rinaningsih, Rinaningsih (Universitas Pendidikan Indonesia, 2024)
This research aims to analyze the impact of the project-based learning model on student’s 21st-Century skills about environmental pollution. This article was written using a meta-analytic research design. This was done using effect size testing by analyzing 7 relevant research publications. Research data can be obtained through online database based on google scholar and semantic scholar. The result of the study of critical thinking skills in the influence test were 3.85 and 4.52 showing that the influence criterion is very high. The result of communication skills research in the influence test were 3.44 and 0.83 showing that the influence criteria were very high and large. The result of research on creative skills in the effect size test are 3.55; 2.94; 1.42 and 5.4 represent very high and large influence criteria. The research result on collaboration skills in the influence test is 0.89 demonstrating large influence criteria. Based on impact test, implementing a project based learning model on student’s 21st-century skills about environmental pollution has a great impact. Through materials on environmental pollution has a great impact. Through materials on environmental pollution using a project based learning model, student’s critical thinking, communication, collaboration and creativity skills can be improved